Effect of Fasting Duration on Total Bacteria and Histopathology in Goldfish Infected with Aeromonas hydrophila - Syifa Fu'ada; Anggieta Ratuyustiarany (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
The purpose of the study was to evaluate the effect of fasting duration on total bacteria as well as changes in intestinal and gills of carp (Cyprinus carpio) after Aeromonas hydrophila infection. The experimental design consisted of five groups, namely negative control, positive control, one-day fasting, two-day fasting, and three-day fasting. Infection is carried out through immersion in a bacterial suspension with a density of 10⁸ colonies per milliliter. The number of bacteria was calculated using the colony calculation technique in the Rimler–Shotts medium, while the histological picture of the intestine and gills was analyzed using hematoxilin–eosin staining. Statistical analysis includes normality tests, one-way variety analysis, and follow-up tests as appropriate. The results showed that fasting had a significant influence on total bacteria and tissue structure. A one-day fast results in the highest total bacteria in the intestines and gills, reflecting acute metabolic stress and decreased mucosal resistance to bacterial colonization. Fasting for two and three days led to a decline in the number of bacteria close to the negative control group, signaling physiological adaptation and stabilization of the microbiota. Intestinal histopathology shows mild lesions in the form of epithelial desquamas, decreased mucous producing cells, and immune cell infiltration, while the gills experience inflammation with reduced severity at a longer duration of fasting. Overall, the duration of the fast determines the effectiveness of the carp's physiological response to infection. Very short fasts increase the burden of bacteria and tissue disorders, while longer fasts provide a protective effect through histological adaptation and microbiota balance.